RANCANG BANGUN WEBSITE AUDIT ENERGI - Muhammad Ilham Margatama; Rini Nur Hasanah; n/a Nurussa’adah (Jurnal Mahasiswa TEUB, 2023)
This study aims to create a website audit energy. With this website, it is hoped that the energy audit mechanism and audit database storage will be simpler, easier, more efficient, and widely used. This energy audit website design uses JavaScript. In the process of designing an energy audit website, processing and storing load data uses the cloud as a database. This load data will be connected to the website appearance through the reading process in the listing writing program. So, the architecture is front and access the API on the server. The server stores data in the cloud. This research was conducted in 4 experimental buildings with different loads. The IKE values for buildings used in the first, second, third and fourth trials are 12.7430 kWh/m²/month and 152.9160 kWh/m²/year, 1.9127 kWh/m²/month and 22.9524 kWh/m²/year, 21.3067 kWh/m²/month and 255.6804 kWh/m²/year, and 4.974 kWh/m²/month and 59.688 kWh/m²/year. From the calculation of IKE per month, it can be concluded that the use of electrical energy in the first, second, third and fourth buildings falls into the categories of quite efficient, quite efficient, wasteful and very efficient. The costs incurred per month for the first, second, third and fourth buildings are IDR 5,522,972.52, IDR 552,655,538, IDR 2,154,729.598, and IDR 5,748,871.59. Calculations using the website and also manually have the same value, so the website is functioning properly. From the similarity of results obtained, it shows that the website is running well. Using this website can make it easier to audit a building, shorten time, can be accessed anytime and anywhere as long as there is aninternet connection, and is cost effective. Keywords: Energy Audits, Clouds Computing, JavaScript, NodeJs, ReactJs